Physiological impact of Tabata exercise on cardiometabolic and cardiorespiratory parameters in transgender people of Multan - Bibi, Amna; Khan, Imran Ahmad; Khalid Khan, Maliha; Ishaq, Shahid (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate factors directly related to cardiometabolic and cardiorespiratory fitness in transgender people. Method: The cross-sectional, experimental study was conducted at the Government Girls Comprehensive Higher Secondary School, Multan, Pakistan, from January to February 2023, after approval from the ethics review committee of the Muhammad Institute of Medical and Allied Sciences, Multan, and comprised transgender people aged 17-28 years. Data was collected using the physical activity readiness questionnaire. All the participants were subjected to Tabata sessions for 4 weeks. Standard cardiometabolic and cardiorespiratory fitness values were noted at baseline and post-intervention. Data was analysed using SPSS 23. Results: Of the 44 participants, 26(59%) were trans-men, 18(40.9%) were trans-women, 16(36.3%) were aged 17-19 years, and 10(22.7%) had other transgender individuals in their families. Cardiorespiratory and cardiometabolic parameters showed significant improvement post-intervention compared to baseline values (p<0.05). Conclusion: Tabata exercises were found to be useful in maintaining cardiorespiratory and cardiometabolic parameters as well in increasing the participants’ motor performance. Key Words: Cardiorespiratory fitness, Transgender persons, Social isolation, High-intensity interval training.